Structure and crystallinity of water dispersible photoactive nanoparticles for organic solar cells1. Issue 33 (7th September 2015) - Pedersen, E. B. L.; Pedersen, M. C.; Simonsen, S. B.; Brandt, R. G.; Böttiger, A. P. L.; Andersen, T. R.; Jiang, W.; Xie, Z. Y.; Krebs, F. C.; Arleth, L.; Andreasen, J. W.
<x xml:space="preserve">Abstract</x> By studying water dispersible photoactive nanoparticles used for organic photovoltaic devices, we provide new insights into the internal structure, crystallinity and the previously unreported drastic changes that occur when the particles are cast into a film.